Patient Perception of the Diagnosis Announcement and its Impact on Quality of Life of Patients with Primary Melanoma or Basal Cell Carcinoma - Marie Aymonier; Charles Taieb; Florence Corgibet; Pascal Joly; Jean-Francois Sei; Veronique Chaussade; Caroline Philippe; Khaled Ezzedine; Marie-Aleth Richard (Medical Journals Sweden, 2022)
An improved understanding of the impact of skin cancer on patients' daily life may optimize disease management. This questionnaire survey of adult patients in real-world settings aimed to assess patient perception of the diagnosis announcement, and the impact of the diagnosis on the patients' professional and personal life. Data from 355 patients with melanoma and 320 patients with basal cell carcinoma (BCC) were analysed. Melanoma significantly impacted the couple, and sexual relationships, as well as family and social life, and reduced the patient's libido more significantly than did BCC (all p < 0.05). Melanoma and BCC significantly impacted the patients' professional and personal lives. The word "cancer" used for a BCC announcement has a high anxiety-producing meaning for the patient. The announcement of each skin cancer should be made during a dedicated consultation, with more time devoted to the patient and with specific empathy, in order to improve reassurance of the patient.